Kinetics and Characteristics of Soybean Oil and Protein Extracted by AOT Reverse Micelle Technology - Lifen Zhang; Fusheng Chen; Wen Zhang; Qian Wu (Journal of Chemistry)
The mass transfer process of soybean oil extracted by AOT reverse micelle was determined. Meanwhile, the physicochemical properties of oil and structural properties of protein were also investigated by gas chromatography (GC), Fourier infrared spectrum (FTIR), and amino acid analyzer. The results indicated that the mass transfer model can be set up as 1+2(1-x)-3(1-x)2/3=0.248•exp⁡(-720.8/T)•t. The reaction probably belongs to internal diffusion. The oil extracted by AOT reverse micelle was in better quality according to physicochemical analysis. The soybean protein almost retained its original structure in AOT reverse micelle by FTIR and amino acid analysis. Therefore, AOT reverse micelle is an attractive procedure for extracting oil and protein simultaneously.